Tsar Samuel Against Emperor Basil II: Why Did Bulgaria Loose the Battle With the Byzantine Empire at the Beginning of the 11th century - Ivanov, Ivelin (Studia Ceranea, 2011)
At the beginning of the 11th century, after decades of almost incessant wars with the Byzantine Empire, the Bulgarian state lost its political independence. In many research works on the period in question there is emphasis put on the stabilization of the Empire at the end of the 10th and the beginning of the 11th century as a major factor or a reason for the loss of our political independence for a century and a half. Naturally, the internal political state of affairs in the Bulgarian Tsardom and the decline of its military power resulting from the loss of independence also made it easier for Emperor Basil II to put pressure on the Balkans. This article deals with the issue of the reasons for the decline in the Bulgarian military power at the end of the 10th and the beginning of the 11th century, the changes in the military stratagems observed in the wars of tsar Samuel and his successors to the throne. Why did Samuel avoid pitched battles? Why do the sources speak mostly about lightly-equipped Bulgarian armies? Why did the Bulgarians of the time take over fortresses after prolonged sieges and mainly through starvation and military stratagems? The present article attempts to give an answer to these questions, based on the written sources of the period and the works of historians.